Mediterranean diet improves blastocyst formation in women previously infected COVID-19: a prospective cohort study - Chen, Huijun; Wang, Jing; Guo, Hongxin; Zhao, Qi; Lin, Ge; Hocher, Berthold; Kalk, Philipp; Wang, Zetao; Gong, Fei (Frontiers in Nutrition, 2024)
Objectives: Our study tries to investigate the effect of the Mediterranean diet (MeDiet) on assisted reproductive treatment outcomes in women after COVID-19 infection. Design: A prospective observational cohort study in the Reproductive and Genetic Hospital of CITIC-Xiangya from February 2023 to August 2023. Subjects: A total of 605 participants previously infected with COVID-19 were enrolled. Exposure: None Main outcome measurement: The primary outcomes are oocyte and embryo quality. The secondary outcomes are pregnancy outcomes. Results: A majority of participants (n=517) followed low to moderate MeDiet, and only a small group of them (n=88) followed high MeDiet. The blastocyst formation rate is significantly higher in MeDiet scored 8-14 points women (46.08%), compared to the other two groups (which is 41.75% in the low adherence population and 40.07% in the moderate adherence population respectively) (P=0.044). However, the follicle number on hCG day, yield oocytes, normal fertilized zygotes, fertilization rate, day three embryos (cleavage embryos), and embryo quality are comparable among the three groups. For those who received embryo transfer, we noticed an obvious trend that with the higher MeDiet score, the higher clinical pregnancy rate (62.37% vs. 76.09% vs. 81.25%, P=0.197), implantation rate (55.84% vs. 66.44% vs. 69.23%, P=0.240) and ongoing pregnancy rate (61.22% vs. 75.00% vs. 81.25%, P=0.152) even though the p values are not significant. An enlarging sample size study, especially in a high adherence population should be designed to further verify the effects of MeDiet’s role in improving IVF performance. Conclusion: High adherence to MeDiet is associated with improved blastocyst formation in women after COVID-19 infection. There is also a trend that high adherence to MeDiet might be beneficial to clinical pregnancy, embryo implantation as well as ongoing pregnancy in these women.